Implementação da merenda escolar regionalizada: uma experiência na “E.M.E.F. boca pequena – Anuerá”, área ribeirinha no rio anuerá, no município de cachoeira do Arari ilha de Marajó - CARDOSO, José Macedo (2020)
This monograph deals with the process of implementation of the regionalized school lunch at the Municipal School of Elementary School Boca Pequena - Anuerá, located in the riverside area of the Anuerá river, municipality of Cachoeira do Arari, Marajó Island, with the general objective of analyzing the importance of eating behavior, subsidizing the school with regionalized products produced by the community it self. The methodology used is of a qualitative nature, as it presents a social phenomenon that serves a river in student clientele. The theoreticalcontributionsweredevelopedfromthebibliographicalanddocumentaryresearch. Considering the studies carried out in loco it was possible to realize that the school meals developed in the region do not meet the specificities of the riverside, by using the same system of other regions, however, with the implementation of the regionalized school meals it is possible to meet the community's qualitative desires local school.